The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s13204-021-01695-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the release of ZnO nanoparticles from cement mortars on microbiological models

Abstract: Incorporating zinc oxide nanoparticles (ZnO NPs) into cement mortars may provide additional functions, e.g., self-cleaning and antibacterial or electroconductive ability. However, these NPs are also known for their potential toxicity. During the life cycle of a cement mortar, various abrasive forces cause the release of admixtures to the natural environment. The effect of the released NPs on model microorganisms has not been extensively studied. Previous studies have shown that nanomaterials may affect various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…The advancement and progress of nanotechnology can upgrade the properties of building/construction materials, and thus assist sustainability [148][149][150][151]. There are obvious benefits related to the development of several nano-enabled products; however, there might also be dangers.…”
Section: Environmental and Health Concerns Of Nanomaterials Applications In Construction Industriesmentioning
confidence: 99%
“…The advancement and progress of nanotechnology can upgrade the properties of building/construction materials, and thus assist sustainability [148][149][150][151]. There are obvious benefits related to the development of several nano-enabled products; however, there might also be dangers.…”
Section: Environmental and Health Concerns Of Nanomaterials Applications In Construction Industriesmentioning
confidence: 99%
“…An example of such microorganisms is the opportunistic pathogen Pseudomonas aeruginosa. Extensive research is carried out to understand the properties of biofilms created by these microorganisms [32,60,61], and some of the conducted studies have shown that the viscoelastic properties of these biofilms are resistant to chemical treatment and strong shear forces, allowing to efficiently recover from mechanical damage [62]. So far, the function of rhamnolipids in biofilms, consisting in preserve the pores and channels between microcolonies, enabling the passage of liquid and nutrients within mature biofilms, has been primarily emphasized [61].…”
Section: Reference To Natural Biofilmsmentioning
confidence: 99%
“…In our research, we focused on the influence of rhamnolipids on the mechanical properties of an alginate hydrogel. Rhamnolipids is a group of biosurfactants, which are produced by many microorganisms, including the most studied opportunistic pathogen Pseudomonas aeruginosa [31,32]. They are classified as glycolipids and consist of a mono-or disaccharide molecule connected by a glycosidic bond to a fatty acid.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nanoparticles, such as silver, copper, or zinc oxide, are used as one of the components to enhance the antimicrobial properties of paper packaging. Zinc oxide is widely used in research concerning electronics, photocatalysis, sensors, construction materials, and medicine [ 13 , 14 ]. It is considered GRAS (generally recognized as safe) by the U.S. Food and Drug Administration (FDA) and can be used as a part of food packaging [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%